EVALUATION OF ANEMIA PREVENTION PROGRAMS AND MATERNAL KNOWLEDGE IN KARAWANG - Maetuti, Maetuti; Hardiana, Hedy (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Brief background: Anemia in pregnancy is a significant public health issue in Indonesia, with a prevalence of 27.7% in 2023. In Karawang Regency, anemia contributes to the high maternal mortality rate due to hemorrhage. Research objectives: This study aimed to evaluate the implementation of the anemia prevention program and analyze the relationship between pregnant women's understanding and the incidence of anemia at community health centers in Karawang Regency. Methods used: This study used a mixed-method design conducted from April to July 2025 in two community health centers in Karawang Regency. A qualitative approach was used to evaluate the program's input, process, and output components through in-depth interviews with 8 key informants. Concurrently, a quantitative approach with a cross-sectional design was employed to analyze the level of understanding among 120 pregnant women and its association with their anemia status. Summary of results: The qualitative evaluation revealed that program implementation was constrained by the input component (human resources and dedicated budget availability), but the process (iron-folic acid supplementation, maternal classes, ANC) and output (targeting and timeliness) components met the standards. Quantitatively, 68.3% of pregnant women had a good understanding of anemia prevention. Statistical analysis showed a highly significant relationship between maternal understanding and the incidence of anemia (p-value < 0.001), where women with poor understanding had a 3.6 times higher risk of being anemic (PR 3.641; 95% CI 2.244-5.909). Conclusion: Although the technical implementation of the anemia prevention program is adequate, weaknesses in the input aspect and a non-uniform level of understanding remain major challenges. Maternal understanding is proven to be a crucial factor in anemia prevention. Therefore, this study recommends the development of the